2023
DOI: 10.1007/s00432-023-05317-6
|View full text |Cite
|
Sign up to set email alerts
|

Hsa_circ_0041150 serves as a novel biomarker for monitoring chemotherapy resistance in small cell lung cancer patients treated with a first-line chemotherapy regimen

Yang Zhang,
Fengmei Chao,
Lihua Lv
et al.

Abstract: Purpose To explore the potential of circRNAs as biomarkers in non-invasive body fluids for monitoring chemotherapy resistance in SCLC patients. Methods CircRNAs were screened and characterized using transcriptome sequencing, Sanger sequencing, actinomycin D treatment, and Ribonuclease R assay. Our study involved 174 participants, and serum samples were collected from all chemotherapy-resistant patients (n = 54) at two time points: stable disease an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Zhang and co-authors demonstrated that it promotes both cancer progression and cisplatin resistance in SCLC models, suggesting this circRNA has a role as a biomarker for monitoring chemotherapy resistance in patients treated with cisplatin-based chemotherapy. They showed its higher value as a diagnostic biomarker with respect to traditional cancerassociated markers such as CA125, CA211, and ProGRP in SCLC and its modulation in the function of treatment response, passing from an already higher value present in patients compared to healthy people, which tends to decrease when the patient responds to therapy and then rises again when resistance appears [81].…”
Section: Extracellular Vesicles (Evs) In Sclcmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang and co-authors demonstrated that it promotes both cancer progression and cisplatin resistance in SCLC models, suggesting this circRNA has a role as a biomarker for monitoring chemotherapy resistance in patients treated with cisplatin-based chemotherapy. They showed its higher value as a diagnostic biomarker with respect to traditional cancerassociated markers such as CA125, CA211, and ProGRP in SCLC and its modulation in the function of treatment response, passing from an already higher value present in patients compared to healthy people, which tends to decrease when the patient responds to therapy and then rises again when resistance appears [81].…”
Section: Extracellular Vesicles (Evs) In Sclcmentioning
confidence: 99%
“…[80] Extracellular vesicles hsa_circ_0041150 / EVs hsa_circ_0041150 could be a biomarker for monitoring chemotherapy resistance in SCLC patients. [81] NLRP6 / By activating NLRP6, SCLC-derived exosomes cause the immunosuppression of distant macrophages, promoting systemic metastasis.…”
Section: Evsmentioning
confidence: 99%